2015
DOI: 10.1038/cddis.2015.117
|View full text |Cite
|
Sign up to set email alerts
|

Che-1 modulates the decision between cell cycle arrest and apoptosis by its binding to p53

Abstract: The tumor suppressor p53 is mainly involved in the transcriptional regulation of a large number of growth-arrest- and apoptosis-related genes. However, a clear understanding of which factor/s influences the choice between these two opposing p53-dependent outcomes remains largely elusive. We have previously described that in response to DNA damage, the RNA polymerase II-binding protein Che-1/AATF transcriptionally activates p53. Here, we show that Che-1 binds directly to p53. This interaction essentially occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…AATF, also called che‐1, is a transcriptional factor that is highly conserved among eukaryotes . AATF is known to promote cell proliferation and also survival by inducing cell cycle arrest, autophagy, DNA repair, and inhibition of apoptosis . Recent studies have shown that AATF is up‐regulated in breast and lung cancer and leukemia .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AATF, also called che‐1, is a transcriptional factor that is highly conserved among eukaryotes . AATF is known to promote cell proliferation and also survival by inducing cell cycle arrest, autophagy, DNA repair, and inhibition of apoptosis . Recent studies have shown that AATF is up‐regulated in breast and lung cancer and leukemia .…”
mentioning
confidence: 99%
“…(11,12) AATF is known to promote cell proliferation and also survival by inducing cell cycle arrest, autophagy, DNA repair, and inhibition of apoptosis. (13)(14)(15)(16)(17) Recent studies have shown that AATF is up-regulated in breast and lung cancer and leukemia. (18)(19)(20) The role of AATF in HCC in the setting of NAFLD and the associated molecular mechanisms were not known.…”
mentioning
confidence: 99%
“…Importantly, we show that the function of AATF in ribosome synthesis is independent of p53. Still, the described role of AATF as a transcriptional regulator and p53 interactor (71) is highly interesting in light of the fact that ribosome synthesis and cellular stress response pathways are strongly interwoven. Defects in ribosome synthesis, often referred to as ‘nucleolar stress’, are known to elicit p53 stabilization by a post-transcriptional mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This binding occurs at the early stage of the DDR and specifically directs p53 toward the transcription of genes involved in cell cycle arrest. Notably, the two proteins detach when DNA damage is not repairable and cells undergo apoptosis ( Desantis et al, 2015a ). Evidence also shows that upon DNA damage phosphorylated-Che-1/AATF, by ATM and Chk2, promotes the transcription of the anti-apoptotic factor XIAP, an inhibitor of caspase activity.…”
Section: Che-1/aatf Is Involved In the Cellular Response To Differentmentioning
confidence: 99%